Effects of moderate- versus mixed-intensity rowing training on physiological responses and performance in highly trained adolescent rowers: A pilot study - Panascì, M.; Di Gennaro, S.; Ferrando, V.; Bisio, A.; Filipas, L.; Ruggeri, P.; Faelli, E. (International Journal of Sports Physiology and Performance, 2025)
Purpose: In rowing, the effectiveness of adding high-intensity interval training (HIIT) to moderate-intensity continuous training (MICT) within the weekly training program on physiological adaptations and performance is still unclear. This study compared the effects of HIIT plus MICT (MIXED) versus MICT alone on physiological/metabolic responses and performance in adolescents.